Evaluation of MyTeen – a SMS-based mobile intervention for parents of adolescents: a randomised controlled trial protocol - Chu, Joanna Ting Wai (BMC Public Health, 2018)
BACKGROUND: Parents play an important role in the lives of adolescents and efforts aimed at strengthening parenting skills and increasing knowledge on adolescent development hold much promise to prevent and mitigate adolescent mental health problems. Innovative interventions that make use of technology-based platforms might be an effective and efficient way to deliver such support to parents. This protocol presents the design of a randomised controlled trial to investigate the effectiveness of a SMS-based mobile intervention (MyTeen) for parents of adolescents on promoting parental competence and mental health literacy. METHODS: A parallel two-arm randomised controlled trial will be conducted in New Zealand, aiming to recruit 214 parents or primary caregivers of adolescents aged 10–15 years via community outreach and social media. Eligible participants will be allocated 1:1 into the control or the intervention group, stratified by ethnicity. The intervention group will receive a tailored programme of text messages aimed at improving their parental competence and mental health literacy, over 4 weeks. The control group (care-as-usual) will receive no intervention from the research team, but can access alternative services if they wish, and will be offered the intervention programme upon completion of a 3-month post-randomisation follow-up assessment. Data will be obtained at baseline, post intervention (1-month), and 3-month follow up. The primary outcome is parental competence assessed by the Parental Sense of Competence Scale at 1-month follow up. Secondary outcomes include: mental health literacy; knowledge of help-seeking; parental distress; parent-adolescent communication; and programme satisfaction. DISCUSSION: To our knowledge this is the first randomised controlled trial on the effectiveness of delivering a parenting support intervention for parents of adolescents solely via a SMS-based mobile intervention. If effective, it could have great potential to reach and support parents of adolescents. TRIAL REGISTRATION: Australian New Zealand Clinical Trial Registry (ACTRN12618000117213) Registered on 29/01/2018.